A community for students.

Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

cathyangs

  • 4 years ago

Disprove this proof of the statement 2=1 a=b a^2=ab a^2-b^2=ab-b^2 (a-b)(a+b)=b(a-b) ((a-b)(a+b))/(a-b)=(b(a-b))/(a-b) a+b=b b+b=b 2b=b 2=1

  • This Question is Closed
  1. nenadmatematika
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    when you divide with (a-b) in the fifth line, you must know that it's only possible when a is not equal to b, otherwise you will get dividing by zero which is not possible....so you can't divide by a-b because your condition in the first line is a=b

  2. cathyangs
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    nice catch! :D I gave this to my dad (a "Permanent-head-damage") and he laughed when he saw it.

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy

Your question is ready. Sign up for free to start getting answers.

spraguer (Moderator)
5 → View Detailed Profile

is replying to Can someone tell me what button the professor is hitting...

23

  • Teamwork 19 Teammate
  • Problem Solving 19 Hero
  • You have blocked this person.
  • ✔ You're a fan Checking fan status...

Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.

This is the testimonial you wrote.
You haven't written a testimonial for Owlfred.